Evaluation of Paxillin Expression in Odontogenic Cysts and Tumors - Azadeh AndisheTadbir; Tina Shid-Moosavi; Fateme Gharibpour; Sahar Arabizadeh (Shiraz University of Medical Sciences, 2024)
Statement of the Problem: Paxillin (PXN) is one of the proteins involved in cell adhesion. PXN and integrins constitute a key site for the focal adhesion between the cell and extracellular matrix. Several studies have shown that PXN is a factor in tumor formation, progression, invasion, and metastasis.Purpose: This study evaluated PXN expression in four types of odontogenic lesions with different aggressive behaviors.Materials and Method: In this retrospective cross-sectional study, PXN expression was immunohistochemically assessed in 68 paraffin-embedded tissue samples from patients with the confirmed diagnosis of four types of odontogenic lesions, including 14 dentigerous cysts (DC), 20 odontogenic keratocyst (OKC), 16 unicystic ameloblastoma, and 18 solid ameloblastoma. The PXN expression in these samples were scored based on the percentage and intensity of immunoreactivity, and compared among the groups by Chi-square test.Results: The PXN marker was detected in the cytoplasm of tumor cells (unicystic and solid ameloblastoma) and the epithelial layer of cysts (DC and OKC). The intensively stained marker of PXN was observed in 9 cases (64.3%) of the DC, 14 cases (70%) of OKC, 12 cases (75%) of unicystic ameloblastoma, and 13 cases (72.2%) of solid ameloblastoma. However, there was not statistical difference of PXN protein expression between DC and OKC (p Value = 0.51) and unicystic and solid ameloblastoma (p = 0.58), also the same was true for cysts and tumors (p = 0.37).Conclusion: The expression of PXN is not related to the biological behaviors of odontogenic lesions.